Analisis Harga Pokok Produksi untuk Penentuan Harga Jual pada Industri Tahu Mulyono Desa Kampung Delima Curup Timur - Nurhidayat Romadhan; Upi Niarti; Paddery; Feri; Nia Natalia; Hongki Sutrisno (Politeknik Raflesia Press, 2026)
The purpose of this research is to determine the cost clarification applied by the Mr. Mulyono Tofu Industry in calculating the cost of goods sold (COGS) and determining the selling price. The analysis used in this research is a qualitative method, involving the analysis of numerical data or quantitative calculations. The results of this study conclude that the Mr. Mulyono Tofu Industry in East Curup uses the Full Costing method in calculating the cost of goods sold (COGS). The calculation of the cost of goods sold (COGS) using the Full Costing method is Rp. 322, while the company estimates it to be Rp. 315. The COGS using the Full Costing method is slightly higher than the company's calculation.